Nutrition: The position in English to-day - M'Gonigle, G. C. M. (George Cuthberth Mura), -1939 (London : Industrial Christian Fellowship)
1936-11 1936 1930s 15 pages [Picture] The Westminster Press 11 Henrietta Street W.C.2 15X/2/217/2